Rating Banks: Risk and Uncertainty in an Opaque Industry - Morgan, Donald P (American Economic Review, 2002)
The pattern of disagreement between bond raters suggests that banks and insurance firms are inherently more opaque than other types of firms. Moody's and S&P split more often over these financial intermediaries, and the splits are more lopsided, as theory here predicts. Uncertainty over the banks stems from certain assets, loans and trading assets in particular, the risks of which are hard to observe or easy to change. Banks' high leverage, which invites agency problems, compounds the uncertainty over their assets. These findings bear on both the existence and reform of bank regulation.